The Common National Curricular Base and law n(o) 13.415/2017: education of young brazilians back to years of lead - Ponciano, Jessica Kurak [UNESP]; Castange, Ronaldo Desiderio [UNESP]; Canhoto de Lima, Marcia Regina [UNESP]; Lima, Jose Milton de [UNESP] (Univ Federal Santa Maria, 2019)
The purpose of this article is to reflect and reflect on the similarities between Law 13.415 / 2017, which was drawn up after the parliamentary coup of 2016 and Law No. 5.692 / 1971 created after the military coup of 1964. The analysis we undertook, to identify the effects and conceptions of both on education for the popular youth. To support this reflection, the following works were used as basic texts: Educational Policy, by Eneida Oto Shiroma, Maria Celia Marcondes de Moraes and Olinda Evangelista; and The New Law of Education: LDB, trajectories, limits and perspectives, by Demerval Saviani. The choice of the theoretical framework that will support the analysis was due to the importance they have for the understanding of Brazilian public educational policies. After a critical reading of Law No. 13,415 / 2017, comparing it to the analyzes of Law No. 5,692 / 1971, undertaken by the authors of the above mentioned works, we conclude that both legislations seek to break with the propaedeutic character of High School and; in addition, they aim to provide education for the youth of the working classes, relegating to them a teaching of a purely technical character, whose main purpose consists in the formation of labor and inputs to the neoliberal capitalist market.
Keywords: Popular Youth Education; Law No.13.415/2017; Common National Curricular Base (BNCC)